PERAN MAJELIS TA’LIM NURUL MUTTAQIN DALAM PEMBENTUKAN AKHLAK REMAJA DI DESA SITIREJO LEMAH DUWUR KECAMATAN WAGIR KABUPATEN MALANG - Fitroh Nur Musyarofah; Abdul Jalil; Lia Nur Atiqoh Bela Dina (VICRATINA, 2021)
Lack of attention and interest in islamic religious education in children on adolescent morals. Terefore, the formation of bad morals into good morals must be carried out regulary and directed, as is the case with praticipating in the Nurul Muttaqin ta’lim assembly. Whit this background, this research has a research focus, namely, to find out how the role of the Nurul Muttaqin ta’lim assembly in the formation of adolescent morals in Sitirejo Lemah Duwur Village. By using a qualitative approach and using the type of case study research is data collected in the from of pictures, written or spoken words from the people observased, this research is not in the from of numbers and not statistical data. From the results of observations and interviews that researchers have done, researchers found the results of the role of the Nurul Muttaqin congregation in the formation of adolescent morals, namely: inviting the community to be good citizens and parents for their children, inviting youth to familiarize and instilling the teachings of islam, providing aplace for teenagres and the community to study religious knowledge.